UPAYA MENINGKATKAN HASIL BELAJAR SISWA TENTANG SUMBER DAYA ALAM MELALUI PENDEKATAN KONTEKSTUAL DALAM PEMBELAJARAN IPA SISWA PADA KELAS VI - Rutnan Bajeneti; Andi Nurwati; Sabrina Nadjib Mohamad (Al-mujahidah, 2026)
This study aims to improve the learning outcomes of sixth-grade students of SDN 21 Limboto, Gorontalo Regency in science subjects, especially natural resources, through the application of a contextual approach. The type of research used is Classroom Action Research (CAR) which is carried out in two cycles, each consisting of planning, implementation, observation, and reflection stages. The subjects of the study were 21 students, consisting of 11 boys and 10 girls. The results of initial observations showed low student learning outcomes, where only 19.5% achieved the Minimum Completion Criteria (KKM). After the application of the contextual approach in the first cycle, learning completeness increased to 28.57%, and in the second cycle it increased significantly to reach more than 85% of students who completed. The application of the contextual approach has been proven to be able to improve student learning outcomes, because students find it easier to relate the material to everyday experiences, are more active in discussions, and are motivated to learn. Thus, the contextual approach is effective for improving student learning outcomes in science learning in elementary schools.